How to improve gold extraction in heap leaching - Azañero Ortiz, Angel (2000)
In some cases it is easy to extract the gold present in an ore by conventional methods cyanidation heap , but in others, the results are very poor and may have originated in mineralogical intergrowths in atomic or sub - atomic size , presence of elements cianicidas and content of fine materials , our research is aimed at finding alternative precious metal , causing severe losses in the tailings gold . work is to show in what circumstances must bind the mineral to solve the problem when a solution presents interesting gold ore fines content and clay materials that are compact when wet and does not allow the cyanide used as a solvent , have mass reach reagent consumption, % moisture : contact with the poor percolation of leaching solutions , characteristic of a good binder machines used to bind minerals, determine the most appropriate economic binder and technically , the different effects are obtained when studying variables such as , curing time , addition of cyanide in the agglomeration step etc . The cost per agglomerate fluctuates around 10% of the total cost of operation is largely compensated by increasing the recovery of precious metals.